Developing a deeper understanding of positive customer feedback - Linda Nasr; Jamie Burton; Thorsten Gruber (2018)
The purpose of this paper is to highlight the importance and extend the understanding of the underresearched concept of personal Positive Customer Feedback (PCF). By comparing and contrasting Front-Line Employees’ (FLEs) and customers’ perspectives, this study aims to develop a deeper understanding of the main elements, characteristics of PCF, its various impacts, and the perceived importance of this phenomenon for both parties. An exploratory research study was conducted using a novel integrated methodological approach combining two well-established qualitative techniques: structured Laddering interviews and various elements of the Zaltman Metaphor Elicitation Technique (ZMET). In total, personal interviews with 40 participants consisting of 20 customers and 20 FLEs were conducted. This study conceptualizes personal PCF in the service literature by identifying the various PCF elements and characteristics. We extend PCF understanding beyond what the current literature shows (i.e. gratitude, compliments) by identifying nine characteristics of PCF. This study also proposes a number of impacts on both customers and FLEs. While both customers and FLEs have a similar understanding of the various elements and characteristics of PCF, the significance of the various elements and the subsequent impacts vary between the two groups. Finally, three key themes in PCF handling that help position PCF within the extant customer management literature are identified and discussed. This study contributes to a well-rounded understanding of customer feedback by counter-balancing the prevailing focus on customer complaining behaviour and proposing a complimentary look at the positive valence of personal feedback. It also provides managerial implications concerning the management of positive service encounters, an emerging topic within service research. This multidisciplinary study is the first to extend the understanding of personal PCF by comparing and contrasting customers’ and FLEs’ perspectives. The findings of this study highlight the need to explore the positive side of service interactions in order to create positive service experiences.